Balkans into Southeastern Europe, 1914-2014 : a century of war and transition - Lampe, John R. (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2014)
'The states and peoples of Southeastern Europe have been divided by wars over the twentieth century, but they have since worked to re-establish themselves into the European mainstream. This timely new edition has been revised, updated and expanded in the light of the latest scholarship and recent events. John R. Lampe now offers a comprehensive assessment of the full century from the Sarajevo assassination in 1914 through to EU membership and developments up to the present day'--
List of Maps and Tables -- Preface -- Introduction: Decades of War, Decades of Transition -- 1. Balkan States and Imperial Borderlands before the Balkan Wars -- 2. Balkan Wars, First World War, Postwar Settlements, 1914-1922 -- 3. Struggling with Liberal and National Transitions in the 1920s -- 4. Illiberal Directions During the Depression Decade -- 5. World War, Civil War, and the Communist Advantage -- 6. Communist and Cold War Transitions, 1945-1963 -- 7. Continuity and Contradictions, 1964-1989 -- 8. New Trials of War and Integration, 1989-2014.
Includes bibliographical references (pages 338-344) and index.
Keywords: Balkan Peninsula -- History -- 20th century; Balkan Peninsula -- History -- 21st century; Balkan Peninsula -- History, Military; Balkan Peninsula -- Relations -- Europe; Europe -- Relations -- Balkan Peninsula